The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/tri.13123
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional treatments before liver transplantation for hepatocellular carcinoma: a study from the European Liver Transplant Registry

Abstract: Locoregional treatment while on the waiting list for liver transplantation (Ltx) for hepatocellular carcinoma (HCC) has been shown to improve survival. However, the effect of treatment type has not been investigated. We investigate the effect of locoregional treatment type on survival after Ltx for HCC. We investigated patients registered in the European Liver Transplant Registry database using multivariate Cox regression survival analysis. Information on locoregional therapy was registered for 4978 of 23 124 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 24 publications
2
41
0
1
Order By: Relevance
“…Even though NASH related cirrhosis is still less frequent in Europe compared with the US, it is anticipated to become the leading indication for LT within the next decade. In terms of results, all the indications have shown an improvement of survival especially HCC, mainly because of a better selection of patients, and the increasing effectiveness of down-staging techniques [18]. The ELTR cohort of patients has also established that some rare malignant tumors like hepatic hemangiosarcoma should be considered absolute contraindications for LT [19], while others like hereditary hemorrhagic telangiectasia [8] or hepatic epithelioid hemangio-endothelioma represent a good indication even in the presence of limited extrahepatic disease [12,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though NASH related cirrhosis is still less frequent in Europe compared with the US, it is anticipated to become the leading indication for LT within the next decade. In terms of results, all the indications have shown an improvement of survival especially HCC, mainly because of a better selection of patients, and the increasing effectiveness of down-staging techniques [18]. The ELTR cohort of patients has also established that some rare malignant tumors like hepatic hemangiosarcoma should be considered absolute contraindications for LT [19], while others like hereditary hemorrhagic telangiectasia [8] or hepatic epithelioid hemangio-endothelioma represent a good indication even in the presence of limited extrahepatic disease [12,24].…”
Section: Discussionmentioning
confidence: 99%
“…A sample of these studies is cited in the references of the manuscript. With reports concerning LT for specific hepatic diseases [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], analysis of the impact of the type of preservation solution [25], and of the immunosuppressive regimen on the patient outcome [26], ELTR has helped develop risk models for mortality following liver-transplantation [27,28]. Owing to the large cohort of patients, the exhaustiveness, and quality of the data, and the long follow-up provided by the ELTR, the results are really representative of LT in Europe.…”
Section: Previous Eltr Achievementsmentioning
confidence: 99%
“…Neoadjuvant locoregional therapy (LRT) is an established treatment option in HCC patients considered for LT to both decrease the waiting list dropout rate and downstage tumors to meet transplant eligibility . Presence of partial necrosis after LRT has been identified as a major risk factor for tumor recurrence after LT …”
mentioning
confidence: 99%
“…(1) Neoadjuvant locoregional therapy (LRT) is an established treatment option in HCC patients considered for LT to both decrease the waiting list dropout rate (2,3) and downstage tumors to meet transplant eligibility. (3)(4)(5)(6) Presence of partial necrosis after LRT has been identified as a major risk factor for tumor recurrence after LT. (7)(8)(9)(10)(11)(12) A large, monocenter study (13) reported a very low HCC recurrence rate (<3% within 5 years) in patients with complete histological response after LRT compared to 10%-15% of tumor recurrence observed in patients meeting Milan criteria at explant pathology. These results were confirmed by a recent multicenter study, where only 5% of patients with no evidence of residual vital tumor (RVT) in explant histopathological exams showed a 5-year HCC recurrence compared to 40% of recurrences observed in patients having an RVT ≥2 cm.…”
mentioning
confidence: 99%
“…Case series and cohort studies have demonstrated that RFA may reduce the dropout rate of HCC patients on the waiting list for liver transplantation to 0–25% [76]. …”
Section: Resultsmentioning
confidence: 99%